Nanoscale Imaging of Live Cells with Confocal Interferometric Scattering Microscopy (iSCAT) - Küppers, Michelle; Albrecht, David; Kashkanova, Anna; Lühr, Jennifer; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2022)
Nanoscale imaging with confocal interferometric scattering microscopy (iSCAT) provides label-free information on subcellular processes and enables tracking of nanoscopic matter such as intracellular vesicles, lipid droplets and viruses.
CRIS-Team Scopus Importer:2022-09-02